PENGEMBANGAN COURSEWARE PADA MATERI SISTEM RESPIRASI UNTUK PEMBELAJARANFISIOLOGI HEWAN - Adeng Slamet (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2016)
Abstract: This study aimed to develop courseware for teaching animal physiology in the material of the respiratory system. Designs in this study refers to research and the development of education (R&D). The procedure of work done in this study design is limited only at the stage of product development to product prototype courseware produced in the material of the respiratory system is ready to be validated by a team of experts (expert judgment) and tested. Therefore, the results obtained and the development presented in this study are: a) The results of the preparation of the program flowchart. Flowchart showed a flowchart depicting the course of learning programs that will be conducted from the beginning to the end of the program; b) Storyboard in the material of the respiratory system. Storyboard contains an overview of learning materials developed with the correct specification. Storyboard developed grounded to the flowchart that have been prepared; and c) Prototype product. In the courseware product in the form of presentation of the information displayed through animation, simulation, still images as well as through text descriptions. Presentation of diverse information was intended to facilitate diversity in terms of interests, learning styles, each of the students, which is expected to meet learning needs. Â Keys Word: Courseware, Respiratory System, Animal Physiology